(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Rolled workpieces are widely used when turning on CNC lathes. The difference between the dimensions and shape of the workpiece and the machine part in these cases is significant and it is necessary to remove the excess of material with the least possible loss of time. This is achieved by means of sequential execution of the work steps (passes) with the corresponding program cycles. Determining the number of passes and the corresponding cutting mode is an optimization problem, which is the subject of the present work.